Dual‐Gate Graphene/h‐BN/GaSe Metal–Insulator–Semiconductor Field‐Effect Transistor (MISFET). Issue 20 (31st May 2022) - Abderrahmane, Abdelkader; Jung, Pan-Gum; Woo, Changlim; Ko, Pil Ju
Abstract : 2D transition metal chalcogenides (TMCs) and dichalcogenides (TMDCs) are promising candidates for next‐generation electronic devices and sensors. Herein, the fabrication and characterizations of back‐gated Si/SiO2 /GaSe‐based (GaSe: gallium selenide) metal–oxide–semiconductor field‐effect transistors (MOSFETs) and top‐gated Gr/h‐BN/GaSe‐based (h‐BN: hexagonal boron nitride) metal–insulator–semiconductor field‐effect transistors (MISFETs) with a common active layer (GaSe) are reported. The morphological, electrical, and optoelectronic properties are investigated, and the device is found to exhibit p‐type behavior with good electrical tunability. At a laser power of 1.147 μW, the device exhibits a photoresponsivity of 90 mA W −1, I ON / I OFF ratios exceeding 10 4, and long decay times. These promising experimental results can promote the application of GaSe‐based MISFETs in multifunctional electronic devices. Abstract : Herein, the fabrication and characterizations of back‐gated Si/SiO2 /GaSe‐based (GaSe: gallium selenide) metal–oxide–semiconductor field‐effect transistors (MOSFETs) and top‐gated Gr/h‐BN/GaSe‐based (h‐BN: hexagonal boron nitride) metal–insulator–semiconductor field‐effect transistors (MISFET) are reported. The device exhibits I ON / I OFF ratio exceeding 10 4, and photoresponsivity of 90 mA W −1 at laser power value of 1.147 μW, which are suitable for electronic device and photodetection applications.